Sleep-Disordered Breathing in Duchenne Muscular Dystrophy: An Assessment of the Literature - Romy Hoque (2016)
Study Objectives:The aim of this review is to review the literature on sleep-disordered breathing in Duchenne muscular dystrophy (DMD).Methods: PubMed was searched with an array of search terms, including "OSA," "obstructive sleep apnea," "sleep-disordered breathing," "muscular dystrophy," "neuromuscular," "Duchenne muscular dystrophy," "polysomnography," and "portable monitoring."All relevant articles were discussed.Results: Eighteen research articles and 1 consensus statement were reviewed, and assessed with relevant data presented.Three early studies prior to 1990 assessed DMD associated obstructive sleep apnea.Five studies assessed positive airway pressure (PAP) ventilation and/or sleep in varying neuromuscular disorders, including a cohort with DMD.Six studies since 2000 include PSG data in exclusively DMD cohorts.Three studies involved portable monitoring (PM).Conclusions: PSG with transcutaneous CO 2 capnography is an important part of the clinical care for those with DMD.The utility of PM in DMD is unclear with only 1 study to date comparing PSG to PM data.Initiation of PAP therapy using bilevel modality may prevent the need for device switching as the disease progresses.